Analysis of the Application of SAK EMKM In Recording Financial Statements at the Orangutan Lodge in Bukit Lawang - Riska Afrillia Putri; Meigia Nidya Sari (CV. AFDIFAL MAJU BERKAH, 2025)
This research is entitled